2008
DOI: 10.1097/01.nne.0000299497.23119.21
|View full text |Cite
|
Sign up to set email alerts
|

Customized Library Tutorial for Online BSN Students

Abstract: Students returning to school to earn advanced degrees frequently experience difficulty accessing and retrieving information necessary to complete assignments. The authors describe the need, the development process, and the outcome of the partnership between nursing faculty and librarians to provide a customized library tutorial for online registered nurse to bachelor of science in nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…For example, one method involves online library tutorials for nursing students (Johnson et al 2010), and another uses a partnership with the library to strengthen nursing research in a distance nursing program (Hallyburton and St. John 2010). Tiered approaches are also described in the literature, with information literacy skills taught across the nursing curriculum (Barnard, Nash, and O'Brien 2005;Carlock and Anderson 2007;Dorner and Taylor 2001;Fetter 2009;Flood, Gasiewicz, and Delpier 2010;Guillot, Stahr, and Plaisance 2005;Innes 2008;Morrison and Krishnamurthy 2008;Schutt and Hightower 2009). Interdisciplinary initiatives are also explicated (Morgan et al 2007).…”
Section: Previous Approaches To Nursing Information Literacymentioning
confidence: 97%
“…For example, one method involves online library tutorials for nursing students (Johnson et al 2010), and another uses a partnership with the library to strengthen nursing research in a distance nursing program (Hallyburton and St. John 2010). Tiered approaches are also described in the literature, with information literacy skills taught across the nursing curriculum (Barnard, Nash, and O'Brien 2005;Carlock and Anderson 2007;Dorner and Taylor 2001;Fetter 2009;Flood, Gasiewicz, and Delpier 2010;Guillot, Stahr, and Plaisance 2005;Innes 2008;Morrison and Krishnamurthy 2008;Schutt and Hightower 2009). Interdisciplinary initiatives are also explicated (Morgan et al 2007).…”
Section: Previous Approaches To Nursing Information Literacymentioning
confidence: 97%
“…4,5,7 Presenting information via online tutorials has been viewed favorably because tutorials are available anytime with an Internet connection. 4,5,7 One study found that online tutorials were an effective alternative to in-person library instruction and were preferred by students. 8 This article attempts to add to the current body of literature by describing in detail one librarian's experiences with creating, promoting, and assessing library tutorials for nursing students.…”
Section: Project Descriptionmentioning
confidence: 99%
“…5,7 Tutorials have been created to help health sciences librarians save time 2 , 9 and to provide distance and online students with library instruction. 4,5,7 Presenting information via online tutorials has been viewed favorably because tutorials are available anytime with an Internet connection. 4,5,7 One study found that online tutorials were an effective alternative to in-person library instruction and were preferred by students.…”
Section: Project Descriptionmentioning
confidence: 99%
See 2 more Smart Citations